Serum urate levels and the risk of hip fractures: data from the Cardiovascular Health Study. - Mehta, Tapan; Bůzková, Petra; Sarnak, Mark J; Chonchol, Michel; Cauley, Jane A; Wallace, Erin; Fink, Howard A; Robbins, John; Jalal, Diana (Metabolism, 2015)
PURPOSE: Uric acid inhibits vitamin D activation experimentally and higher serum urate levels are associated with higher parathyroid hormone levels in humans suggesting a link between uric acid and bone health. We hypothesized that hyperuricemia may increase the risk of fractures in older adults. METHODS: 1963 men and 2729 women ≥65 years of age who participated in the Cardiovascular Health Study and had baseline serum urate levels were included in the study. The primary outcome was incident hip fracture, assessed prospectively through June, 2008 by inpatient and outpatient records. The analysis was stratified by sex a priori. RESULTS: There was a U-shaped relationship between serum urate levels and hip fractures in men. Men in the lowest and the highest urate quartiles (<4.88 and ≥6.88 mg/dL respectively) had a significantly higher rate of fractures in unadjusted analysis. However, upon multivariate adjustment, only the HR for hip fracture in highest quartile versus the reference remained significant (HR 1.9; 95% C.I. 1.1, 3.1; p value 0.02). High serum urate levels were not associated with hip fractures in women. CONCLUSION: In this large prospective cohort of community-dwelling older adults, increased serum urate levels were associated with an increased risk of hip fractures in men. Further studies are needed to confirm these findings and to understand the mechanisms that underlie them.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Cohort Studies; Estrogen Replacement Therapy; Female; Health Surveys; Hip Fractures; Humans; Kaplan-Meier Estimate; Male; Prospective Studies; Risk; Sex Factors; United States; Uric Acid

Variation in resting heart rate over 4 years and the risks of myocardial infarction and death among older adults. - Floyd, James S; Sitlani, Colleen M; Wiggins, Kerri L; Wallace, Erin; Suchy-Dicey, Astrid; Abbasi, Siddique A; Carnethon, Mercedes R; Siscovick, David S; Sotoodehnia, Nona; Heckbert, Susan R; McKnight, Barbara; Rice, Kenneth M; et al. (Heart, 2015)
OBJECTIVE: Resting heart rate (RHR) is an established predictor of myocardial infarction (MI) and mortality, but the relationship between variation in RHR over a period of several years and health outcomes is unclear. We evaluated the relationship between long-term variation in RHR and the risks of incident MI and mortality among older adults. METHODS: 1991 subjects without cardiovascular disease from the Cardiovascular Health Study were included. RHR was taken from resting ECGs at the first five annual study visits. RHR mean, trend and variation were estimated with linear regression. Subjects were followed for incident MI and death until December 2010. HRs for RHR mean, trend and variation are reported for differences of 10 bpm, 2 bpm/year and 2 bpm, respectively. RESULTS: 262 subjects had an incident MI event (13%) and 1326 died (67%) during 12 years of median follow-up. In primary analyses adjusted for cardiovascular risk factors, RHR mean (HR 1.12; 95% CI 1.05 to 1.20) and variation (HR 1.08; 95% CI 1.03 to 1.13) were associated with the risk of death while trend was not. None of the RHR variables were significantly associated with the risk of incident MI events; however, CIs were wide and the MI associations with RHR variables were not significantly different from the mortality associations. Adjusting for additional variables did not affect estimates, and there were no significant interactions with sex. CONCLUSIONS: Variation in RHR over a period of several years represents a potential predictor of long-term mortality among older persons free of cardiovascular disease.
Keywords: Aged; Aged, 80 and over; Cause of Death; Electrocardiography; Female; Follow-Up Studies; Heart Rate; Humans; Incidence; Linear Models; Male; Myocardial Infarction; Outcome Assessment (Health Care); Prognosis; Proportional Hazards Models; Prospective Studies; Rest; Risk Factors; Time; Washington

Soluble Inflammatory Markers and Risk of Incident Fractures in Older Adults: The Cardiovascular Health Study. - Stojanović, Danijela; Bůzková, Petra; Mukamal, Kenneth J; Heckbert, Susan R; Psaty, Bruce M; Fink, Howard A; Cauley, Jane A; Wallace, Erin; Curtis, Lesley H; Hirsch, Calvin; Budoff, Matthew; Li, Dong; et al. (J Bone Miner Res, 2017)
Several in vitro and animal studies have showed that inflammatory markers play a role in bone remodeling and pathogenesis of osteoporosis. Additionally, some human longitudinal studies showed suggestive associations between elevated inflammatory markers and increased risk of nontraumatic fractures. We examined several inflammatory markers and multiple fracture types in a single study of older individuals with extensive follow-up. We assessed the association of four inflammatory markers with the risk of incident hip fractures among 5265 participants of the Cardiovascular Health Study (CHS) and a composite endpoint of incident fractures of the hip, pelvis, humerus, or proximal forearm in 4477 participants. Among CHS participants followed between 1992 and 2009, we observed 480 incident hip fractures during a median follow-up of 11 years. In the composite fracture analysis cohort of 4477 participants, we observed 711 fractures during a median follow-up of 7 years. Adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for hip fracture associated with doubling of IL-6 were HR 1.15 (95% CI, 1.02 to 1.30) overall and HR 1.17 (95% CI, 1.01 to 1.35) in women. We also observed a positive association between each unit increase in white blood cell (WBC) count and risk of hip fracture: HR 1.04 (95% CI, 1.01 to 1.06) overall and HR 1.06 (95% CI, 0.95 to 1.20) in women. We observed no significant associations between any of the four inflammatory markers and a composite fracture endpoint. Our findings suggest that chronic inflammatory and immune processes may be related to higher rates of incident hip fractures. © 2017 American Society for Bone and Mineral Research.